2016
DOI: 10.23937/2469-5793/1510042
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Outcomes of a Community-Based Educational Program for Colorectal Cancer Prevention in Hispanics

Abstract: Objectives: Colorectal cancer (CRC) is the 2nd most diagnosed cancer and leading cause of cancer death in Puerto Rico. However, CRC screening rates remain low. The aim of this study was to test the effectiveness of a Train-the-Trainers’ (TTT) program to develop trainers capable of educating others within their communities about CRC prevention. Methods: The TTT program consisted of didactics and seminars to capacitate participants to become trainers in CRC prevention. This project was evaluated using three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The mean CRC knowledge score obtained in our study is similar to those reported in two previous studies in PR using the same questionnaire. Cruz-Correa et al reported a 9.4 ± 0.5 mean CRC knowledge score among the 115 healthcare professionals that participated in the Train the trainers (TTT) program [23]. Portilla-Skerrett et al obtained a slightly higher mean CRC knowledge score (10.3 ± 0.10) among 154 participants recruited in health fairs in PR [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean CRC knowledge score obtained in our study is similar to those reported in two previous studies in PR using the same questionnaire. Cruz-Correa et al reported a 9.4 ± 0.5 mean CRC knowledge score among the 115 healthcare professionals that participated in the Train the trainers (TTT) program [23]. Portilla-Skerrett et al obtained a slightly higher mean CRC knowledge score (10.3 ± 0.10) among 154 participants recruited in health fairs in PR [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results correlate with the findings of Ma et al [32], who reported that Koreans and Chinese individuals with limited knowledge about CRC were less likely to undergo CRC screening. Also, Tseng et al [23] showed that African Americans who had more CRC knowledge were more likely to undergo CRC screening. However, due to the nature of our study, we cannot determine whether having more knowledge increases adherence to CRC screening or if having undergone CRC screening tests increases CRC knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation